PERLINDUNGAN HUKUM TERHADAP INVESTOR DALAM INVESTASI ILEGAL AKIBAT PROMOSI MEDIA ONLINE INFLUENCER MELALUI AKUN YOUTUBE - Azhari; Khairunnisa Praja (LPPM IAI Almuslim Aceh, 2026)
The rapid development of digital technology and social media has led to the emergence of various forms of investment promotion through YouTube platforms involving influencers. This phenomenon is often exploited by irresponsible parties to offer illegal investment schemes that harm the public, particularly novice investors who are easily influenced by persuasive content. This study aims to analyze the forms of legal protection for investors against illegal investment practices promoted through YouTube influencers and to examine the legal responsibilities of the parties involved. The research method used is normative juridical, employing statutory and conceptual approaches. The results indicate that legal protection for investors has been regulated under various laws and regulations; however, its implementation still faces challenges, especially in monitoring digital content and enforcing laws against influencers who promote illegal investments. Furthermore, there are legal gaps regarding the limits of influencer liability as parties influencing public investment decisions. Therefore, stronger regulations, increased financial literacy, and stricter supervision of promotional content on social media are necessary to prevent investor losses in the future.